Editorial. - Campana, S.; Remondino, F.; Vinci, G.; Fontana, A. (Archaeological Prospection)
The article discusses the challenges of conducting archaeological surveys in wooded areas, particularly in the Mediterranean region, due to the dense vegetation cover. It highlights the increasing use of LiDAR technology for topographical mapping and archaeological survey, which has shown promising results in penetrating woodland canopies to reveal hidden archaeological features. The article presents case studies from various countries, including Italy, Spain, Croatia, Slovenia, and Slovenia, demonstrating the effectiveness of LiDAR in uncovering archaeological landscapes and features that were previously inaccessible. The research emphasizes the potential of LiDAR in transforming archaeological exploration, monitoring, and preservation of cultural heritage sites, particularly in regions with dense vegetation cover like the Mediterranean.